Proceedings of International Conference on Communication and Networks : ComNet 2016 - Modi, Nilesh; Verma, Pramode K.; Trivedi, Bhushan (Springer, 2017)
The volume contains 75 papers presented at International Conference on Communication and Networks (COMNET 2015) held during February 19-20, 2016 at Ahmedabad Management Association (AMA), Ahmedabad, India and organized by Computer Society of India (CSI), Ahmedabad Chapter, Division IV and Association of Computing Machinery (ACM), Ahmedabad Chapter. The book aims to provide a forum to researchers to propose theory and technology on the networks and services, share their experience in IT and telecommunications industries and to discuss future management solutions for communication systems, networks and services. It comprises of original contributions from researchers describing their original, unpublished, research contribution. The papers are mainly from 4 areas - Security, Management and Control, Protocol and Deployment, and Applications. The topics covered in the book are newly emerging algorithms, communication systems, network standards, services, and applications.
Includes author index.
Keywords: Computer networks -- Congresses.; Internet of things -- Congresses.; Cloud computing -- Congresses.; elektronické knihy; electronic books